THE CORRELATION BETWEEN ENGLISH GRAMMAR COMPETENCE AND SPEAKING FLUENCY OF ELEVENTH GRADE STUDENTS IN SMAN 1 SIDOARJO (RETAIN, 2013)
Abstract Among four basic skills of English, speaking can be considered as the most difficult yet the most demanding skill to master. Thus, experts have been trying to find the most effective way to enhance the learners speaking for decades. Unfortunately, there doesn’t seem to be a clear agreement among them. One method focuses more on the speech accuracy while the other emphasizes the fluency. In Indonesia, most English teachers seem keen of implementing grammar based learning even though they know that the curriculum expects that students are able to develop speaking skill which is not only accurate but also fluent. With regards to the aforementioned fact, this study aims to reveal whether there is a significant correlation between students’ grammar competence and their speaking fluency. It is expected that the results of the study can help English teachers make better prediction regarding how far grammar competence correlate with speaking fluency. The study was conducted in SMAN 1 Sidoarjo which one of the leading schools in the province and used descriptive-quantitative research design. Sampling was done randomly with five students being drawn from every eleventh grade class. Based on the acquired data it was discovered that most of the students were fair in terms of English grammar competence and speaking fluency. In addition, the end result of the calculation of r value suggested that students’ English grammar competence moderately correlates with their speaking fluency. Keywords: English grammar competence, Speaking fluency, Eleventh graders, Correlation